1963
DOI: 10.1111/j.1365-2621.1963.tb01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Solubility as Influenced by Physiological Conditions in the Musclea,b,c

Abstract: The solubilities of sarcoplasmic and myofibrillar proteins were determined at the time of slaughter, onset of rigor mortis, completion of rigor mortis and 24 hr after death in muscles exhibiting a wide range of physiological conditions during the post-mortem period.Muscle protein solubility was grossly altered by the conditions of both temperature and pH which existed at the onset of rigor mortis or during the first few 'hours after death. Sarcoplasmic protein solubility at 24 hr was decreased to 55% of that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1
1

Year Published

1966
1966
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(82 citation statements)
references
References 19 publications
5
75
1
1
Order By: Relevance
“…The protein solubility of salted cooked batters is higher in salt-soluble protein solubility than unsalted meat batters (Farouk and Swan, 1997). Sayre and Briskey (1963) reported that protein solubility in meat of important different qualities characteristics is influenced by careful control of the conditions, and that protein solubility appears to provide a better indication of meat product quality. Thus, gels formation in chicken salt-soluble protein heat-induced gel systems can be affected by the concentration and contents of myofibrillar protein, the Means in the treatments with different letters are significantly different (p <0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The protein solubility of salted cooked batters is higher in salt-soluble protein solubility than unsalted meat batters (Farouk and Swan, 1997). Sayre and Briskey (1963) reported that protein solubility in meat of important different qualities characteristics is influenced by careful control of the conditions, and that protein solubility appears to provide a better indication of meat product quality. Thus, gels formation in chicken salt-soluble protein heat-induced gel systems can be affected by the concentration and contents of myofibrillar protein, the Means in the treatments with different letters are significantly different (p <0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Peaks 1 and 2 seemed to exhibit bell-shaped time responses where the area percent of peak 1 decreased at the early time point (8 h) but increased thereafter and that of peak 2 increased 8 h after sacrifice but decreased subsequently. Both rigor mortis and its resolution are well known to affect solubility of a wide range of muscle proteins (Sayre et al, 1963). Given that rigor mortis develops within several hours in mice (Annesley and Walker, 1980), a low amount of peak 1 and a high amount of peak 2 observed at 8 h could be attributed to rigor mortis-mediated changes in solubility of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al (2010) reported that protein solubility profiles are an effective indicator of the degree of protein denaturation during meat processing, particularly that the protein solubility of meat products may affect their textural qualities (Astiasaran et al, 1990). Furthermore, the sarcoplasmic and myofibrillar protein solubilities in different quality meat products are produced under carefully controlled conditions (Sayre and Briskey, 1963). High total protein and sarcoplasmic protein solubilities are important for high quality processed …”
Section: Protein Solubility Of the Chicken Emulsions In Model Systemsmentioning
confidence: 99%